PENERAPAN SOLUTION FOCUS BRIEF COUNSELING UNTUK MENGATASI KECEMASAN AKADEMIK DARING DI SMA N 1 JAKENAN - Nimas Galih Larasati; Indah Lestari; Susilo Rahardjo (Universitas Muria Kudus, 2022)
The objectives of this study are: 1. To find out the factors that cause academic anxiety during online learning, 2. To overcome academic anxiety through the Solution Focus Brief Counseling service.This type of research is a case study with qualitative research methods. The subjects studied were 2 students of class XI SMA N 1 Jakenan who experienced academic anxiety. The analytical method used by the researcher is the bacon induction analysis method, where the analysis will be a reference in analyzing and researching.The results show that researchers in implementing individual counseling using the Solution Focus Brief Counseling approach can overcome academic anxiety during online learning, as evidenced by changes in counselee behavior during online learning. The factors that influence academic anxiety during online learning in Class XI students of SMA N 1 Jakenan come from internal and external factors. Internal factors are caused by feelings of excessive worry and unpreparedness to face online learning. While external factors are caused by demands from parents, environmental conditions that can interfere with concentration and unsupportive facilities.